State-of-the art bicuspid aortic valve repair in 2020 - Ehrlich, Tristan; de Kerchove, Laurent; Vojacek, Jan; Boodhwani, Munir; El-Hamamsy, Ismail; De Paulis, Ruggero; Lansac, Emmanuel; Bavaria, Joseph E; El Khoury, Gebrine; Schäfers, Hans-Joachim (Progress in cardiovascular diseases, 2020)
Patients with a bicuspid aortic valve (BAV) frequently require surgical intervention for aortic regurgitation (AR) and/or aneurysm. Valve-preserving surgery and repair of regurgitant BAVs have evolved into an increasingly used alternative to replacement. Anatomic predictors of possible repair failures have been identified and solutions developed. Using current techniques most non-calcified BAVs can be preserved or repaired. Excellent repair durability and freedom from valve-related complications can be achieved if all pathologic components of aortic valve and root including annular dilatation are corrected. Anatomic variations must be addressed using tailored approaches.
Keywords: bikuspidální aortální chlopeň; anuloplastika srdeční chlopně; aorta; Humans; Aortic valve replacement; Cardiac Valve Annuloplasty; výběr pacientů; Bicuspid aortic valve; Aortic regurgitation; Patient Selection; nemoci srdečních chlopní; Female; Aortic valve repair; Bicuspid Aortic Valve Disease; výsledek terapie; Heart Valve Diseases; lidé; ženské pohlaví; Male; Treatment Outcome; mužské pohlaví; Aorta; aortální chlopeň; Aortic Valve